Program konsultasi sistem administrasi dan pelayanan donor darah sebagai bentuk kepedulian sosial - Muchsam, Yoki; Yuda, Mulfi Sandi; Maulana, M Afrizal; Wiyata, Mariati Tirta; Gunawan, Ce; Febrianti, Intan Rieke (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This study aims to explore the impact of the administrative system consultation programme and blood donation services as a form of social care. The focus of this research is how the effectiveness of the administrative system can increase community participation in blood donation and improve the quality of blood donation services in Bandung City. In addition, the level of public awareness about the importance of blood donation is also a factor that affects the amount of participation. The Business Administration study programme has an important role in developing a better administrative system to improve the efficiency and effectiveness of blood donation services. With a deeper understanding of service management and administrative systems, health institutions can design more effective strategies in promoting blood donation as a form of social care. The importance of improving administrative systems and blood donor services that are more inclusive, efficient, and data-driven to increase community participation in blood donation. By understanding the complexity of challenges in the administrative system of blood donation services, relevant institutions can develop better policies to improve the quality of services, so that blood donation becomes a more organised and accessible activity for the wider community.